Islamic Education Management and Policy (Lembaga Pengembangan Kinerja Dosen, 2025)
In the context of education in Indonesia, education requires many touches from various parties in the formation of its policies. Considering that the moral crisis is increasing, strict education management is needed. Education is a process of instilling and developing implicit values and norms in every subject, including Islamic religious education and also its teachers. Therefore, not only Islamic religious education teachers have the responsibility to educate students' morals and ethics, this responsibility also applies to all educators. Efforts to improve the quality of Islamic religious education have been widely implemented. The goal is none other than to convey the meaning of education that functions to build the character and morals of a dignified nation in order to educate the life of the nation to build the potential of Indonesian people who believe and fear God Almighty, have noble morals , are healthy, knowledgeable, capable, creative and independent. The existence of shortcomings and advantages in each educational institution will have an impact and require different handling. The right policies and handling will have a good impact and be in accordance with the expectations of an institution. On the other hand, if the management and policies are not considered and adjusted to the educational institution , then failure will be encountered. Each educational institution has different needs and objectives according to the needs, interests and goals to be achieved.